Identification of the effect of transglutaminase enzyme on physicochemical properties of Milkfish (Chanos chanos) surimi gel. Issue 1 (September 2020) - Yuliana, I; Mahendradatta, M; Laga, A
Abstract: Surimi is a myofibril protein that is stabilized from the fish flesh, which is mechanically removed, washed with water and mixed with cryoprotectant. The yield of milkfish surimi is quite high at 58.72%, but the strength value of the gel is still not good, while the important quality attribute of a surimi product is its elastic texture in terms of the strength of the surimi gel. One technique to increase the formation of surimi gel is by adding the transglutaminase enzyme. The purpose of this study was to determine the effect of enzyme addition on the physicochemical properties of surimi. The research design consisted of two treatments, namely without enzymes and with the addition of enzymes 0.1 units/g surimi. The research method consisted of two stages, namely preparation of making surimi and surimi gel processing. Observation parameters included gel strength, whiteness, moisture content, and pH. The best research results obtained were the addition of enzymes with physicochemical properties of gel strength (3795 g.cm), whiteness (78.90), moisture content (76.70%), and pH (6.35). The treatment of adding enzymes significantly affected the strength of the gel and the moisture content but did not significantly influenced the whiteness and pH.